God as truth-maker – about Peter Thomas Geach’s conception - Dzięcioł, Mateusz (Hybris, 2023)
This text examines the topic of truthmakers in the philosophy of Peter Thomas Geach, presenting a reconstruction of Geach’s concept and critically analyzing it. The focus is on the connection between mental representations of perceived objects, their linguistic reflection and reality. Additionally, the text explores the concept of God’s causality in St. Thomas Aquinas’ philosophy and compares it with Geach’s approach, highlighting their distinctive features. A formal representation of this relationship is then provided. The central thesis of this theory posits the identification of God with Truth, which allows for the understanding of the verification relationship through the term “voluntaristic causation”. Consequently, following Thomas Aquinas’ proposed terminology, God is categorized as one of the entia actu intelligibilia. However, Geach’s concept lacks in-depth analysis of the matter of person. Another problematic aspect of this concept pertains to the clarification of the ontological category serving as the foundation for verification relations. Difficulties arise when attempting to adapt Geach’s theory to contemporary perspectives that consider states of affairs as the ontological basis for the semantics under consideration. The epistemology employed by the British philosopher relies on the subject-object relationship, akin to God’s causal connection to reality, rather than states of affairs.